Engineering the future, understanding the past a social history of technology - Vleuten, Erik van der; Davids, Mila 1965-; Oldenziel, Ruth 1958- (Amsterdam University Press, 2017)
Technology today is often presented as our best hope of solving the world's social and sustainability problems. And that's nothing new: engineers have always sought to meet the big challenges of their times-even as those challenges have shaped their technology. This book offers a historical look at those interactions between engineering and social challenges, showing how engineers developed solutions to past problems, and looking at the ways that those solutions often bring with them unintended consequences that themselves require solving
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Okt 2018)
Keywords: Sozialgeschichte 1815-2015; Technologie